Análise macroscópica do efeito da adição de nanocerâmica ao concreto - Rodrigo Perfeito Marques de Castro (2009)
Nanoscience and nanotechnology are areas that have a great potential for new materials and new applications development. Recently many researches are using the nanotechnology concept to create Portland concrete composites, where they look for the comprehension of the hydration of cement particles and addition of nanometrics (nm) particles, either nano-silica or nanofibres. In the last decades, the majority of theprogress in the performance of cimentitious materials had been carried through the optimization of the grain stacking and, over all, through the reduction of the capillary porosity with the rational use of chemical additives more and more efficient. This study investigated the effect of the addition of nanoparticles of ceramic montimorillonita at Portland cement concrete. For such, two working conditions were chosen, ratio water /cement (0.45 / 0.50 / 0.55), and the following quantities of nanoceramic 0%, 2% and 4%. We analyzed the following parameters: workability, flux of the water flowing, compressive strength and tensile strength. The addition of nanoceramic caused a reduction in workability, which was expected. The results of axial compression for 28 days showed an improvement of 11% and 14% depending on the ratio water / cement.In the case of tensile strength by diametrical compression, the best option was to 4% of nanoceramic. In this case, the improvement was 6% for the ratio water / cement equal to 0.55 and 18% and 21% for 0.45 and 0.50, respectively. The addition of nanoceramic seems to be an excellent option for the preparation of Portland cement concrete. The nanoceramic presented pozzolanic activity.